2010
DOI: 10.1111/j.1442-2042.2010.02558.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular pathology of chromophobe renal cell carcinoma: A review

Abstract: Abstract:The recognition of chromophobe renal cell carcinoma (RCC) among other distinct types of renal cell tumors (RCT) based on light-microscopic features, such as cytoplasmic and nuclear characteristics, might pose a dilemma in some cases because of morphological pattern overlapping with renal oncocytoma or conventional RCC. The present article reviews chromophobe RCC with focus on aspects of its molecular pathology, which was shown using ancillary modern microarray-based technology that can distinguish it … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 87 publications
(155 reference statements)
2
24
0
Order By: Relevance
“…Preoperative biopsy of kidney tumors is not widely employed (6–9) with only about 10% of all nephrectomies preceded by a diagnostic biopsy. This problem is longstanding, and despite several academic center based studies suggesting adequate histopathological resolution is possible in this setting (25–27), diagnostic uncertainty in the differentiation of benign RO from malignant chRCC (9,10) and in additional cases even with eosinophilic clear-cell RCCs (ccRCC) remains a clear contributing factor to low rates of biopsy in routine practice. Recent reviews by Ng et al (8) and Yusenko (9,10) both concluded that there was no reliable diagnostic marker or IHC algorithm suitable for reliable differential diagnosis of renal tumors.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Preoperative biopsy of kidney tumors is not widely employed (6–9) with only about 10% of all nephrectomies preceded by a diagnostic biopsy. This problem is longstanding, and despite several academic center based studies suggesting adequate histopathological resolution is possible in this setting (25–27), diagnostic uncertainty in the differentiation of benign RO from malignant chRCC (9,10) and in additional cases even with eosinophilic clear-cell RCCs (ccRCC) remains a clear contributing factor to low rates of biopsy in routine practice. Recent reviews by Ng et al (8) and Yusenko (9,10) both concluded that there was no reliable diagnostic marker or IHC algorithm suitable for reliable differential diagnosis of renal tumors.…”
Section: Discussionmentioning
confidence: 99%
“…This problem is longstanding, and despite several academic center based studies suggesting adequate histopathological resolution is possible in this setting (25–27), diagnostic uncertainty in the differentiation of benign RO from malignant chRCC (9,10) and in additional cases even with eosinophilic clear-cell RCCs (ccRCC) remains a clear contributing factor to low rates of biopsy in routine practice. Recent reviews by Ng et al (8) and Yusenko (9,10) both concluded that there was no reliable diagnostic marker or IHC algorithm suitable for reliable differential diagnosis of renal tumors. Ng et al (8) concluded as had Liu and Fanning (26), that there is a group of renal tumors, notably ROs and small chRCCs, where increased confidence in diagnosis would defer or totally eliminate the need for surgical intervention.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Oncocytoma and chRCC are different tumors with different genomic profiles [42,43]. CD82/KAI1 is a marker for distinguishing chRCCs from other types of renal cell tumors, especially from renal oncocytomas with an overlapping phenotype [44].…”
Section: Chromophobe Rccmentioning
confidence: 99%
“…CRCC has its own histological, immunohistochemical, and cytogenetic characteristics (Yusenko 2010). By light microscopy, the tumor cells have a compact growth pattern and the cytoplasm stains lightly with hematoxylin and eosin staining.…”
Section: Introductionmentioning
confidence: 99%